Novel design and simulation of a hybrid solar electricity system with organic Rankine cycle and PV cells - Li, Jing; Pei, Gang; Li, Yunzhu; Ji, Jie (International Journal of Low-Carbon Technologies, 2010)
The proposed system mainly consists of flat-plate compound parabolic concentrators (CPCs) integrated with photovoltaic (PV) cells and organic Rankine cycle (ORC). The technologies of CPC, PV cell and ORC are analyzed, and feasibility of the hybrid solar electricity system is demonstrated. Novel configuration for the hybrid electricity generation is carefully designed to react to different operating conditions. Fundamentals of the innovative system are illustrated, and mathematical models are developed to study the heat transfer and energy conversion processes. The results indicate that the lowtemperature solar thermal power generation integrated PV cells can produce much more electric per unit surface area than side-by-side PV panels and CPC-ORC modules. © The Author 2010. Published by Oxford University Press. All rights reserved.